MECHANISMS INVOLVED IN FIBRIN FORMATION - Boyles, Paul W. (The Rockefeller University Press, 1951)
That the role of thrombin in the conversion of fibrinogen to fibrin is essentially enzymatic, is established not only by the minute amounts of thrombin which are effective but also by the complete independence of fibrin yields and thrombin concentrations over a very wide range of thrombin dilutions and clotting times. The thrombin-fibrinogen reaction, in the phase beyond the "latent period" at least, seems fundamentally "first order." Technical requirements of the experiments leading to these conclusions include: (1) a highly purified (e.g. 97 per cent "clottable") fibrinogen, (2) absence of traces of thrombic impurities in the fibrinogen, (3) absence of fibrinolytic protease contaminant of the thrombin and the fibrinogen, and (4) sufficient stability of the thrombin even at very high dilutions. Four conditions affecting thrombin stability have been investigated. Fibrin yields are not significantly modified by numerous experimental circumstances that influence the clotting time, such as (1) temperature, (2) pH, (3) non-specific salt action due to electrical (ionic) charges, which alter the Coulomb forces involved in the fibrillar aggregation, (4) specific ion effects, whether clot-accelerating (e.g. Ca(++)) or clot-inhibitory (e.g. Fe(CN)(6)''''), (5) occluding (adsorptive) colloids, which have a "fibrinoplastic" action, e.g. (a) acacia and probably (b) fibrinogen which has been mildly "denatured" by salt-heating, acidification, etc. The data with which several European workers have attempted to substantiate the idea of a two-stage thrombin-fibrinogen reaction with an intermediary "profibrin" (allegedly partly "denatured") have been reanalyzed with controls which lead us to very different conclusions, viz. (1) denaturation and fibrin formation are independent; (2) partial denaturation is "fibrinoplastic" (see above); and (3) conditions of strong salinity and acid pH (5.1) usually do not completely prevent the thrombin-fibrinogen reaction but merely prolong the "latent" phase and lessen the time required for completion of essentially the same reaction (fibrin polymerization) when more favorable clotting conditions are restored. Thus, our experiments advance the modern concepts concerning the coagulation mechanisms along lines that, for the most part, agree with those of the Harvard physical chemists, and we oppose the European views concerning a two-stage reaction, "profibrin," and "the denaturase theory" of clotting.